The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1413-81232014197.09722013
|View full text |Cite
|
Sign up to set email alerts
|

Suicídio e trabalho em metrópoles brasileiras: um estudo ecológico

Abstract: Suicídio e trabalho em metrópoles brasileiras: um estudo ecológicoSuicide and work in Brazilian metropolises: an ecological study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
19

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
3
8
0
19
Order By: Relevance
“…Other studies (19)(20) have also demonstrated the result evidenced here, indicating that suicide of workers may be related to mental suffering resulting from the work itself. Countries such as France and Japan have data on workrelated suicide, which is attributed to an intensification of work and overwork, to the lack of solidarity between the work team and psychological and moral harassment.…”
Section: Discussionsupporting
confidence: 84%
“…Other studies (19)(20) have also demonstrated the result evidenced here, indicating that suicide of workers may be related to mental suffering resulting from the work itself. Countries such as France and Japan have data on workrelated suicide, which is attributed to an intensification of work and overwork, to the lack of solidarity between the work team and psychological and moral harassment.…”
Section: Discussionsupporting
confidence: 84%
“…that corroborate this study. 6 In a descriptive, retrospective, quantitative approach on mortality from external causes in young adults in Teresina-PI, from 2001 to 2011, based on official and secondary data from the Department of Information Technology of the Unified Health System ( DATASUS) and the Mortality Information System (MIS) of the Ministry of Health, the most revealed sociodemographic characteristics were race/color brown (70.67%), followed by white (12.82%), single civil status (71.74%), then married (21.89%) and schooling, with a majority between four and seven years of schooling (35.82%), followed by schooling from eight to 11 years (22.63%), information similar to this study. 13 In a study carried out in the Barbacena microregion, using a population from the period 2003 to 2009, similar data were obtained with the current research, a growing percentage of deaths due to suicide in the brown color/race (10.1%), followed in the period 1980 to 2005, the authors did not manage to link race/color as a factor for suicide, considering that 50% of the records did not presented this variable.…”
Section: Resultsmentioning
confidence: 99%
“…Nos estudos realizados em Barra do Garças, não há essa análise 1 . No país, o sexo masculino tem maior prevalência de suicídio 8 , porém no sexo feminino há maior taxa de tentati vas, correspondendo a 66,65% do total 5,7 . Em Barra do Garças, os dados referentes às tentati vas condizem, pois as mulheres somam 70,1% do total 4 , o que demonstra que, tanto em nível nacional quanto na região analisada, as mulheres são responsáveis pelo maior número de atentados à própria vida.…”
Section: Discussionunclassified
“…6,7 . O sexo masculino teve maior prevalência de suicídio 8 , com uma razão que variou entre 3:1 e 7,5:1 3,9 . No sexo feminino, ocorreu maior taxa de tentati vas, correspondendo a 66,65% do total 5,7 .…”
Section: Métodounclassified